2005
DOI: 10.1302/0301-620x.87b3.15694
|View full text |Cite
|
Sign up to set email alerts
|

The blood supply of the common peroneal nerve in the popliteal fossa

Abstract: We investigated the blood supply of the common peroneal nerve. Dissection of 19 lower limbs, including six with intra-vascular injection of latex, allowed gross and microscopic measurements to be made of the blood supply of the common peroneal nerve in the popliteal fossa. This showed that a long segment of the nerve in the vicinity of the fibular neck contained only a few intraneural vessels of fine calibre. By contrast, the tibial nerve received an abundant supply from a constant series of vessels arising di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…In addition, patients in our series were treated with a variety of interventions, including neurolysis and nerve and tendon transfers, which have been previously demonstrated to improve recovery and function [9,16,21]. Despite surgical treatment, the peroneal nerve has a poor intrinsic ability for recovery, perhaps as a result of its variable and diminished intraneural blood supply [15]. Previous studies have demonstrated that most peroneal nerve injuries occur in the setting of posterolateral corner injuries as a result of poor tolerance of the nerve to accommodate stretch with changes in limb position during trauma [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, patients in our series were treated with a variety of interventions, including neurolysis and nerve and tendon transfers, which have been previously demonstrated to improve recovery and function [9,16,21]. Despite surgical treatment, the peroneal nerve has a poor intrinsic ability for recovery, perhaps as a result of its variable and diminished intraneural blood supply [15]. Previous studies have demonstrated that most peroneal nerve injuries occur in the setting of posterolateral corner injuries as a result of poor tolerance of the nerve to accommodate stretch with changes in limb position during trauma [22,25].…”
Section: Discussionmentioning
confidence: 99%
“…After the regression and involution of the axial artery, the accompanying artery of the sciatic nerve remains in adults, proximal to the tendinous opening of the adductor magnus muscle where during the embryological period the axial artery anastomoses with the developing femoral artery, and continues inferiorly as the popliteal artery [Kadiyala et al, 2005]. In all cases the accompanying artery of the sciatic nerve is detected as rudimentary blood vessel.…”
Section: Discussionmentioning
confidence: 99%
“…A recent opinion is that ischemia of the nerve as a result of thrombosis or embolism of the blood vessels has an important role in the postoperative paralysis of the nerve. For example, paralysis of the common peroneal nerve occurred very often after intra-aortic dilatation, iliac endarterectomy, aortoiliac bypass or femoral arteriography [Kadiyala et al, 2005]. Taking into the consideration that peripheral nerves get segmental vascularization from the neighboring muscular and cutaneous branches or arterial main trunks, the question that arises is: are all nerves or all segments of the nerve sufficiently supplied and are collateral anastomoses sufficiently developed to prevent ischemia of the nerves?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations